Recurrence after exenteration for canine orbital malignant schwannoma - Kang, Seonmi (J Vet Sci, 2017)
A 14-year-old Maltese dog presented with progressive exophthalmos and external deviation of the right eye. Ultrasonography revealed the presence of a retrobulbar mass and fine-needle aspiration cytology was performed, which detected a malignant mass. There was no evidence of metastasis on thoracic and abdominal radiography. Computed tomography showed no invasion into the bony orbit and no metastasis to the lung or lymph nodes. Exenteration was performed to remove the mass completely. Malignant peripheral nerve sheath tumor was confirmed by histopathological examination.